2021
DOI: 10.1371/journal.pone.0254994
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 percent positivity and risk factors among people with HIV at an urban academic medical center

Abstract: Since the onset of the COVID-19 pandemic, it has been unclear how vulnerable people with HIV (PwH) are to SARS-CoV-2 infection. We sought to determine if PwH are more likely to test positive for SARS-CoV-2 than people without HIV, and to identify risk factors associated with SARS-CoV-2 positivity among PwH. We conducted a cross-sectional study in which we collected electronic medical record data for all patients who underwent SARS-CoV-2 PCR testing at an academic medical center. Presence of HIV and other chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…In our study, 78% (68/87) of the participants presented with hypertension, HIV, diabetes, Tuberculosis (Tegally et al), and chronic pulmonary disease. Suspected cases who had HIV were not at increased risk of SARS-CoV-2 positivity, consistent with previous studies ( Charre et al, 2020, Friedman et al, 2021, Inciarte et al, 2020. Our study was underpowered to evaluate whether HIV-infected cases had worse outcomes, but studies elsewhere have suggested HIV is not associated with worse outcomes ( Cooper et al, 2020, Nagarakanti et al, 2021.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, 78% (68/87) of the participants presented with hypertension, HIV, diabetes, Tuberculosis (Tegally et al), and chronic pulmonary disease. Suspected cases who had HIV were not at increased risk of SARS-CoV-2 positivity, consistent with previous studies ( Charre et al, 2020, Friedman et al, 2021, Inciarte et al, 2020. Our study was underpowered to evaluate whether HIV-infected cases had worse outcomes, but studies elsewhere have suggested HIV is not associated with worse outcomes ( Cooper et al, 2020, Nagarakanti et al, 2021.…”
Section: Discussionsupporting
confidence: 83%
“…The data are provocative because the cutoff point was seen at the relatively high level of <500 cells/mm 3 , although more data are needed to validate this finding. Prior studies largely conducted during ancestral strain time periods have not found an increased prevalence of SARS-CoV-2 among PWH compared to HIV-uninfected people [ 13–16 ]. VoC that exhibit levels of resistance to the immunodominant epitopes associated with immune protection may be a factor in these differences [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that PwH acquiring SARS-CoV-2 was a factor that drove telehealth use among PwH. We have previously examined patterns in SARS-CoV-2 testing among PwH at our institution during this time period and found that overall SARS-CoV-2 positivity among PwH was 7.2% [ 28 ]. Most of these patients were Black (90.3%) and had a median age of 49 (34–59) years of age, suggesting to us that it is unlikely that infection with SARS CoV-2 is responsible for the racial disparity in telehealth use that we observed.…”
Section: Discussionmentioning
confidence: 99%